The South African Journal of Industrial Psychology: A comparison of scholarly publications and published practitioner concerns from 2014-2017 - Van Der Westhuizen, Steven (School of Management Studies, 2020)
This study identified the trending domains and content themes found in the South African Journal of Industrial Psychology (SAJIP) from 2014 to 2017. These trends were then compared with those in the South African Journal of Human Resource Management (SAJHRM), Deloitte Human Capital Trends Reports, and related Google search data over the same period. This was done through a content analysis, documenting the frequencies and percentages of HPCSA domains and content themes that are present in each of the four sources, including across 218 studies in the two academic journals. Results revealed that while there were similar trends found in the SAJIP and SAJHRM, when these are compared to the Deloitte Human Capital Trends report and Google Trends results, it is concluded that much of the I-O Psychology research does not address the concerns of those operating as practitioners. The insights gathered through the study suggest that further efforts are required to understand and align research in the South African Journal of Industrial Psychology to the concerns of HR practitioners in South Africa.